Key figures on Europe - 2016 edition (Luxembourg, 2016)
"Key figures on Europe presents a selection of topical data. Most data cover the European Union and its Member States, while some indicators are provided for other countries, such as members of EFTA, enlargement countries to the European Union. This publication may be viewed as an introduction to European statistics and provides a starting point for those who wish to explore the wide range of data that is freely on Eurostat’s website. "